Screeing of Patients with Essential Hypertension as a Prevention Method Hypertensive Nephropathy - M. M. Batyushin; A. A. Galushkin; A. S. Litvinov; N. A. Sadovnichaya; D. S. Tsvetkov; L. I. Rudenko; O. M. Mamedova (Медицинский вестник Юга России, 2012)
Purpose: To determine prevalence and evaluate the risk of hypertensive nephropathy in patients with hypertension.Materials and Methods: Based on the city polyclinic № 16 Rostov-on-Don and the Center for Restorative Medicine and Rehabilitation, the mines was carried out screening of patients with hypertension. The study included 330 hypertensive patients without chronic kidney disease in history, of which 303 (91.8%) patients were male, 27 (8.2%) patients – women.Results: It was found that not all clinical and laboratory parameters are affecting the risk of kidney damage in patients with high blood pressure.Summary: Hypertension leads to irreversible renal disorders, assessment of risk is an integral part of the MT treatment activities conducted in these patients.